Travelling Through Troubled Landscapes - Motut-Firth, Monique (Ecocene: Cappadocia Journal of Environmental Humanities, 2022)
Traveling through a warehouse filled with magazines, her Doukhobor grandparent’s house and a reclaimed landfill Motut-Firth weaves a story between physical spaces, eras and the physical impacts of image theory on human activity and the environment. How do commercial images contribute the changing geography of our anthroposcenic moment? Navigating from the personal into the general, Motut-Firth guides us through historical Canadian imagery and leads us to the physical impacts of consumerism, spurred she argues by the glut of shiny seductive consumer images that celebrate human production and social status. Her collage based scrap-systems and animation shorts play with commercial images produced in different eras and disciplines. They invent new ways of understanding (or confusing) the complexity of our visual moment in time. She wades and sifts through our collective past of paper imagery as an unconventional archivist looking for clues to where we are now and where we will be in the future.